Diet with isolated soy protein reduces oxidative stress and preserves ventricular function in rats with myocardial infarction - Hagen, Martine Kienzle (2009)
We investigated the effects of an isolated soy protein (ISP) diet offered over a 9-week period to rats in whom myocardial infarction (MI) had been induced, and a casein diet given as a control. Male Wistar rats were assigned to six groups after infarct size determination (n Z 8/group): Sham Casein (SC); Infarct Casein < 25% (IC < 25%); Infarct Casein > 25% (IC > 25%); Sham Soy (SS); Infarct Soy < 25% (IS < 25%); and Infarct Soy > 25% (IS > 25%). MI surgery was performed at the fifth week, and one month later, the animals were hemodynamically assessed to evaluate left ventricular systolic pressure (LVSP), left ventricular end diastolic pressure (LVEDP), contractility and relaxation indexes (dP/dt). Lung and liver specimens were also collected for the estimation of organ congestion. Oxidative stress was evaluated in heart homogenates through chemiluminescence (CL), carbonyl groups, and antioxidant enzyme activities of superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GPx). Infarcted groups treated with casein showed cardiac hypertrophy, lung and liver congestion, increased LVEDP and decreased LVSP and dP/dt, all typical signals of heart failure. Ventricular dysfunction was correlated with increased myocardial oxidative damage as seen by CL and carbonyl groups data in the groups IC < 25% and IC > 25% (3 and 10-fold increase, respectively). The ISP diet was able to improve ventricular systolic and diastolic function in the groups IS < 25% and IS > 25% (LVEDP was reduced by 44% and 24%, respectively) and to decrease myocardial oxidative stress. The overall results confirm the preventive role of soy-derived products in terms of post-MI myocardial dysfunction probably by an antioxidant action.